2011
DOI: 10.1183/09031936.00079111
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and acute exacerbations

Abstract: Recent evidence indicates that acute exacerbations of chronic obstructive pulmonary disease aggravate the extrapulmonary consequences of the disease. Skeletal muscle dysfunction, a sustained decrease in exercise tolerance, enhanced symptoms of depression and fatigue are reported. Avoidance of physical activities is likely to be a key underlying mechanism and increases the risk of new exacerbations. Pulmonary rehabilitation is an intervention targeting these systemic consequences. Exercise strategies need to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
7

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 154 publications
(181 reference statements)
0
33
0
7
Order By: Relevance
“…Keeping in mind the deleterious effects of exacerbations on limb muscles, several interventions to prevent or counteract muscle impairment have been considered (522). These interventions, mainly based on exercise training, have been used during, immediately after, or late after the exacerbation (523).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…Keeping in mind the deleterious effects of exacerbations on limb muscles, several interventions to prevent or counteract muscle impairment have been considered (522). These interventions, mainly based on exercise training, have been used during, immediately after, or late after the exacerbation (523).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…Istotnym elementem w zapobieganiu zaostrzeniom może być rehabilitacja oddechowa [202] oraz operacyjne zmniejszanie objętości płuc [203].…”
Section: Profilaktyka Zaostrzeń Pochpunclassified
“…59 Several investigators have shown that NMES intervention is well tolerated and effective alone or in combination with exercise, results in improvements in strength, muscle mass, exercise capacity, and sense of dyspnea during daily living activities in patients with very severe COPD, chronic heart failure, and mechanically ventilated intensive care unit patients who experience intolerable symptoms during or after active training due to the progression of their underlying disease. 12,22,60,61 It has been suggested that applying the NMES as a home-based NMES program maintains and improves quadriceps femoris muscle strength in patients with lung cancer. 62,63 Randomized-controlled trials are needed to study the efficacy and safety of NMES for severely disabled lung cancer patients.…”
Section: Physical Inactivitymentioning
confidence: 99%
“…14,75 Even though in lung cancer, cough is helped with medication, it has been stated that hydration, gentle suctioning, postural drainage, chest physiotherapy, and external oscillation applications can be useful for patients with lung cancer, underlying COPD and bronchiectasis who have poor cough reflex to maintain bronchial hygiene. 5,7,9,14,23,25,61 Unfortunately, there are no studies in this area. Since the risk of metastasis is high in patients with advanced lung cancer, it is sensible to avoid the percussive applications on the chest wall (percussion, vibration, etc.).…”
Section: Cough and Respiratory Secretionsmentioning
confidence: 99%